The conclusions drawn from ventilation/perfusion single photon emission computed tomography (SPECT) compared to lung perfusion SPECT and a chest x-ray (CXR) in patients with suspected pulmonary pulmonary thromboembolism - Abubakar, Sofiullah (Department of Radiation Medicine, 2019)
Purpose: There are conflicting results from studies on whether the ventilation (V) scintigraphy can be safely omitted or replaced by a chest x-ray. These studies were based on planar ventilation perfusion (V/Q) scintigraphy. We evaluated the value of the V single photon emission computed tomography (SPECT) on the final conclusion drawn from a V/Q SPECT and the possible role of the chest x-ray as a surrogate for the V SPECT. Methods Raw data of V/Q SPECT images and chest x-ray acquired within 48 hours over 18 months period were retrieved, reprocessed and reviewed in batches. The V SPECT, Q SPECT and chest x-ray were reviewed separately and in combination. Data on the presence and character of defects and chest x-ray abnormalities were recorded. The V/Q SPECT images were interpreted using the criteria in the EANM guideline and the Q SPECT and chest x-ray images were interpreted using the PISAPED criteria. Agreement between the diagnosis on the V/Q SPECT review and the Q SPECT and chest x-ray review was analysed. Results 21.1% of the patients were classified as 'PE present’ on the V/Q SPECT review whereas 48.9% were classified as 'PE present’ on the Q SPECT and chest x-ray review. Only 5.4% of defects seen on V SPECT had matched chest x-ray lung field opacity. Conclusion Our study showed that the omission of a V SPECT led to a high rate of false positive diagnoses and that the ventilation scan cannot be replaced by a chest x-ray.